2019
DOI: 10.1071/wr17151
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating movement patterns to discern habitat selection: black bears as a case study

Abstract: Context Animals’ use of space and habitat selection emerges from their movement patterns, which are, in turn, determined by their behavioural or physiological states and extrinsic factors. Aim The aims of the present study were to investigate animal movement and incorporate the movement patterns into habitat selection analyses using Global Positioning System (GPS) location data from 16 black bears (Ursus americanus) in a fragmented area of Florida, USA. Methods Hidden Markov models (HMMs) were used to discern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…Based on the results of our HMM analyses, we distinguished three biologically relevant behavioral states generally based on patterns in the movement characteristics of wild pigs (i.e., resting, foraging, traveling). Previous studies have identified similar patterns for other species 11 , 37 , 55 ; however, behavioral states associated with movement characteristics may be assigned differently depending on prior knowledge of different animal species and fix rate at which GPS data were collected. Specifically, the interpretation of a behavioral state associated with short to intermediate step-lengths (what we defined as foraging) may differ among species.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Based on the results of our HMM analyses, we distinguished three biologically relevant behavioral states generally based on patterns in the movement characteristics of wild pigs (i.e., resting, foraging, traveling). Previous studies have identified similar patterns for other species 11 , 37 , 55 ; however, behavioral states associated with movement characteristics may be assigned differently depending on prior knowledge of different animal species and fix rate at which GPS data were collected. Specifically, the interpretation of a behavioral state associated with short to intermediate step-lengths (what we defined as foraging) may differ among species.…”
Section: Discussionmentioning
confidence: 74%
“…Specifically, the interpretation of a behavioral state associated with short to intermediate step-lengths (what we defined as foraging) may differ among species. For example, this category of behavior was defined as “locally active at the kill site” for wolves 56 , “moderately active” for Florida panthers 57 , and “encamped” for American black bears 55 . However, for caribou, this intermediate behavioral state was assigned as “foraging” and was associated with a foraging behavior for black bears as well 11 , 55 .…”
Section: Discussionmentioning
confidence: 99%
“…An important question, here, is how an eagle might balance scavenging road-killed carrion with the risk of vehicle collision across different behavioral or physiological states. State-specific selection in SSFs is an active area of analytical development (Hooten et al, 2014; Avgar et al, 2016; Hooten et al, 2017; Karelus et al, 2019; Scharf et al, 2019), and while our SSF did not explicitly incorporate behaviorally-specific selection into its framework, we were still able to infer behavior-specific use of linear features and habitat plus seasonal variation in those patterns (Figs. 4-6).…”
Section: Discussionmentioning
confidence: 99%
“…An important question here is how an eagle might balance scavenging road-killed carrion with the risk of vehicle collision across different behavioural or physiological states. State-specific selection in SSFs is an active area of analytical development (Avgar et al, 2016;Hooten et al, 2014Hooten et al, , 2017Karelus et al, 2019;Scharf et al, 2019), and while the el-SSF did not explicitly incorporate behaviourally specific selection into its framework, we were still able to infer behaviour-specific use of linear features and habitat plus seasonal variation in those patterns (Figures 4-6). While progress is being made (e.g.…”
Section: Extending Ssfsmentioning
confidence: 97%